Gene Expression and Polymorphism of Interleukin-36a in Psoriatic Iraqi Patients - Mahmood, Aseel S.; Ibraheem, Muntaha R.; Ibraheem, Shaima R. (Iraqi Journal of Science, 2025)
Psoriasis is a common, persistent papulosquamous skin illness that affects people of all ages and has a high societal and personal burden. It is associated with various serious medical conditions like depression, psoriatic arthritis, and cardiometabolic syndrome. Interleukin-36a (IL-36a) is a key molecule in inflammation, coordinating the activation of critical pro-inflammatory cytokines and immune cells. The current study involved 84 Iraqi psoriatic patients (PoS) and 67 healthy controls. Real-time PCR and sequencing techniques were used to evaluate the gene expression and polymorphism of two SNPs (rs2305152 A/C and rs895497 G/A) of the IL-36a gene. The findings revealed that the IL-36a gene was up-regulated in psoriatic patients (1.29 [IQR: 1.12-1.55]) compared to healthy individuals. When we looked at how IL-36a gene activity varied based on specific genetic variations, only rs2305152 had a significant effect; the CC genotype was associated with significantly higher expression compared to the AA genotype (2.12 [IQR: 1.57-3.47] vs. 1.15 [IQR: 1.04-1.47]; p = 0.009). The genotypes of the SNPs showed that the AC genotype of IL-36a SNP rs2305152 (A/C) and GA genotype in rs895497 (G/A) presented a significantly amplified incidence in patients with psoriasis in comparison with the healthy control, and the associated OR values were 17.91 and 0.10, respectively. Hardy-Weinberg equilibrium value of SNP rs2305152 (A/C) was p-HWE = 0.033 in PsO. The haplotypes (rs2305152 A/C and rs895497 G/A) of the IL36A gene showed high significance. The results showed that the linkage disequilibrium values of IL-36a SNPs rs2305152 and rs895497 had a correlation coefficient value of R2 = 0.09 and an LD coefficient value of D’ = 0.68, indicating that certain genetic variation (AC for rs2305152 and GA for rs895497) were more common in psoriasis patients compared to the control group, suggesting a potential association with the condition. This study suggests that the genetic variation rs2305152 (A/C) in the IL-36a gene may play a role in the risk of psoriasis.